FEATURES OF THE TERRITORIAL AND FUNCTIONAL ORGANIZATION OF THE BIG CITY (ON THE EXAMPLE OF THE CITY OF KHARKIV) - Вірченко, Павло; Мазурова, Анастасія (Human Geography Journal, 2014)
In article, questions of the territorial and functional organization of the city of Kharkiv at the present stage are considered. Separate demographic indicators of the city of Kharkiv on its administrative regions, which directly or mediately, influence the territorial and functional organization of the city, are analysed. According to a technique of functional zoning of territories, three main zones are characterized: residential, landscape and recreational and production that, usually, allocate within the cities. Residential zoning of the territory of the city of Kharkiv is given in article and the main directions of modern development of a residential zone of the city are analysed. Landscape and recreational zoning of the territory of the city of Kharkiv is opened and security with green zones and green plantings of administrative regions of the city is analysed. On the basis of the analysis of volumes of the realized production the main directions of development of industrial zones of the city of Kharkiv are considered. The most intensive directions of a development of the city of Kharkiv on the functionality are defined.